2003
DOI: 10.1021/ja030496v
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Apoptolidin:  Completion of the Synthesis and Analogue Synthesis and Evaluation

Abstract: The total synthesis of apoptolidin (1) is reported together with the design, synthesis, and biological evaluation of a number of analogues. The assembly of key fragments 6 and 7 to vinyl iodide 3 via dithiane coupling technology was supplemented by a second generation route to this advanced intermediate involving a Horner-Wadsworth-Emmons coupling of fragments 22 and 25. The final stages of the synthesis featured a Stille coupling between vinyl iodide 3 and vinylstannane 2, a Yamaguchi lactonization, a number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
44
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 21 publications
1
44
0
3
Order By: Relevance
“…Syntheses of apoptolidinone A, the aglycone of 1, were reported by the groups of Sulikowsky [143], Crimmins [144], Nicolaou [138][139][140], and Koert [141,142]. In addition, several studies on the synthesis of fragments of apoptolidinones have been reported [137,[145][146][147][148][149][150][151][152][153][154][155].…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…Syntheses of apoptolidinone A, the aglycone of 1, were reported by the groups of Sulikowsky [143], Crimmins [144], Nicolaou [138][139][140], and Koert [141,142]. In addition, several studies on the synthesis of fragments of apoptolidinones have been reported [137,[145][146][147][148][149][150][151][152][153][154][155].…”
Section: Methodsmentioning
confidence: 94%
“…Successful total synthesis of 1 has been achieved by the groups of Nicolaou [138][139][140] and Koert [141,142]. Syntheses of apoptolidinone A, the aglycone of 1, were reported by the groups of Sulikowsky [143], Crimmins [144], Nicolaou [138][139][140], and Koert [141,142].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Die in jüngster Zeit zunehmend beobachtete Resistenz von Bakterien verleiht der Antibiotika-Forschung allerdings besondere Dringlichkeit. Wer konnte in diese Thematik besser einführen als C. Walsh (Harvard Medical School), der durch Monographien [1] und jüngst als Herausgeber eines ganzen Heftes der Chemical Reviews [2] [4] und Koert [5] (Apoptolidin) sowie Crimmins (Apoptolidinon) [6] synthetisiert worden war, erforderte das ganze Spektrum der modernen stereoselektiven Synthesechemie. Die Synthese umfasste nur 14 Stufen in der längsten linearen Sequenz.…”
unclassified
“…Implementation of this "top down" strategy in our laboratory has thus far led to a higher yielding isolation procedure, to the identification of isoapoptolidin (4), 7 an isomer of apoptolidin that forms during isolation and assay, and to the synthesis and biological evaluation of numerous semi-synthetic analogs 8 which have uncovered new aspects of its mode of action. In the course of these studies we have also identified several new apoptolidins.…”
mentioning
confidence: 99%